Integrating Maqashid Syariah in Sustainable Development Goals (SDGs): A Conceptual Framework for Green Economic Policy - Sadly, Effendi (International Journal of Economics (IJEC), 2026)
This study develops a quantitative framework for integrating Maqashid Syariah principles within Sustainable Development Goals (SDGs) implementation for green economic policy in Indonesia. Employing a quantitative research design with panel data analysis covering 2018-2024, this research examines the relationship between Islamic finance development and SDG achievement across 34 provinces. The study constructs a Maqashid-SDG Integration Index comprising five dimensions: preservation of religion (hifz ad-din), life (hifz an-nafs), intellect (hifz al-aql), progeny (hifz an-nasl), and wealth (hifz al-mal). Data from Bappenas, OJK, Ministry of Finance, and BPS reveal that Islamic finance assets reached IDR 2,582 trillion in 2023, representing 10.95% market share, while green sukuk issuance totaled USD 6.9 billion since 2018. Statistical analysis demonstrates a significant positive correlation (r=0.742, p<0.01) between Islamic finance penetration and SDG performance indicators. Regression results indicate that a 1% increase in Maqashid-aligned financing contributes to 0.63% improvement in environmental SDG indicators. The findings validate that integrating Maqashid Syariah into SDG frameworks enhances policy effectiveness for green economic transition, with Indonesia's SDG index reaching 70.22 in 2024. This research provides policymakers with a measurable framework to optimize Islamic finance mechanisms for sustainable development outcomes